선거관리위원회의 제도와 조직, 그리고 선거품질: ELECT 데이터를 활용한 경험적 분석 - 최재동; 조진만 (의정논총, 15(2), 2020)
본 연구는 ‘선거품질 프로젝트(Electoral Integrity Project)’에서 2016년 수행한 ‘선거교육과 역량 훈련(ELECT)’ 데이터를 활용하여 한국 선관위의 제도적 특성을 국가 간 비교연구를 통하여 고찰하고, 선관위 조직 운영이 구성원의 선거품질에 대한 인식에 어떠한 효과를이끄는지를 경험적으로 분석하고 있다. 본 연구의 분석 결과, 한국의 선관위는 독립성과전문성, 인력 규모, 교육훈련, 예산으로 평가한 제도적 측면에서 다른 국가들과 비교하여우수한 특징을 보였다. 또한 선관위 직원들의 역량, 동기, 기회 요인 가운데 역량 요인이선거품질에 유의미한 영향을 미치는 것으로 나타났다. 본 연구는 그동안 큰 주목을 받지못하였던 한국 선관위의 제도적 특성을 국가 간 비교연구를 통하여 고찰하고, 조직 운영이선관위 구성원들의 선거품질에 대한 인식에 중요한 영향을 미친다는 점을 경험적으로 밝혀냈다는 점에서 중요한 의미를 가질 수 있다. 뿐만 아니라 본 연구의 결과는 양극화가 심화되고 있는 정치환경 속에서 선거품질 향상을 위한 선관위의 위상과 역할을 재정립하는데 다양한 시사점을 제공할 수 있을 것으로 기대된다. This study analyzes the Electoral Learning and Capacity Training (ELECT) data developed by the Electoral Integrity Project to understand the relationship between the National Election Commission of Korea's institutional design and workforces, and electoral integrity. The study finds that NEC gains higher scores in terms of institutional design including independence, professionalism, training opportunities, workforce magnitude, and budget than other countries in comparison do. Additionally, only ability of NEC staffs seems to affect electoral integrity among the Ability-Motivation-Opportunity factors. Results indicate that NEC staffs' demand for ability might come from challenging workloads and perceived unfair promotion opportunities. The article makes a contribution to the literature on electoral integrity by investigating Korean electoral management body's institutional design and staffs, understudied so far. It also provide lessons about the role of NEC for fair electoral management in the politically polarized environment. KCI Citation Count: 0